Exemplary of Limang: The Life Story of Rakoetta Sembiring Brahmana as “Bupati Pejuang” 1914-1964 - Suprayitno Suprayitno (Universitas Gadjah Mada, 2019)
Rakoetta S. Brahmana is a name that is still unfamiliar to some of the ears of North Sumatra people, especially for Indonesians in general. Rakoetta, as her comrade and family called her, was a Karo son who was born in the village of Limang, Tanah Karo on August 4, 1914. Rakoetta means glue in the Karo language. By giving that name, his parents hoped that Rakoetta would truly become the glue (unity) for the family and the wider community. This article is intended to re-record the struggle and dedication of Rakoetta as an exemplary figure for what is now known a “fighting” in the Indonesian politics, the Simultaneous Local Election. Rakoetta understood his sociological conditions and Karo culture well because of the influence of his parents. His knowledge of Karo culture became a strong capital in pursuing his political career during the independence struggle in North Sumatra, in addition to his formal education experience at HIS Kabanjahe and Medan Taman Siswa School between 1924 and 1930s. When in Medan, Rakoetta began to come into contact with ideas of nationalism. In Medan political organizations such as Budi Utomo, Sarekat Islam, the Indonesian Communist Party and the Indonesian National Party flourished. During the revolutionary period of independence he was actively involved as a member of Partindo, PNI, Boempa, BPI, BKR until he became regent of the revolutionary period. Rakoetta continued to serve as a Regent of Karo for two periods from 1946 to 1954, and again a Regent of Asahan concurrently Mayor of Tanjung Balai 1954-1960 and Mayor of Siantar 1960-1964. Rakoetta passed away in 1964. The story of Rakoetta’s life saves a bitter and full of ethos of struggle; consistent, resilient, tough, creative, clean and anti-corruption. There are many moral examples that should be emulated from a Rakoetta. The story of his struggle has never been written by anyone.